Durability of Antibody Responses to SARS-CoV-2 Infection and Its Relationship to Disease Severity Assessed Using a Commercially Available Assay - Alanoud Alshami; Rabab Al Attas; Hadeel Anan; Aroub Al Maghrabi; Salim Ghandorah; Amani Mohammed; Abdulbary Alhalimi; Jumana Al-Jishi; Hadi Alqahtani (Frontiers in Microbiology, 2021)
Background: Assessing the humoral immune response to SARS-CoV-2 is crucial for inferring protective immunity from reinfection and for assessing vaccine efficacy. Data regarding the durability and sustainability of SARS-CoV-2 antibodies are conflicting. In this study, we aimed to determine the seroconversion rate of SARS-CoV-2 infection in a cohort of reverse-transcriptase polymerase chain reaction (RT–PCR)-confirmed SARS-CoV-2 infections and the antibody dynamics, durability, and the correlation of antibody titers with disease severity using the commercially available SARS-CoV-2 anti-spike (S1/S2) protein.Methods: A total of 342 subjects with PCR-confirmed COVID-19 were enrolled. A total of 395 samples were collected at different time points (0–204) after the onset of symptoms or from the day of positive PCR in asymptomatic patients. Demographics, clinical presentation and the date of PCR were collected. All samples were tested using the automated commercial chemiluminescent system (DiaSorin SARS-CoV-2 S1/S2 IgG) on the LIAISONXL® platform (LIAISON).Results: The seroconversion rate for samples collected 14 days after the onset of infection was much higher than that for samples collected before 14 days (79.4% vs. 39.4%). The rate of seroconversion in symptomatic participants (62.1%) was similar to that of asymptomatic participants (56.1%) (p = 0.496). The IgG titer distribution was also similar across both groups (p = 0.142), with a median IgG level of 27.86 AU/ml (3.8–85.5) and 15 AU/ml (3.8–58.85) in symptomatic and asymptomatic participants, respectively. However, IgG titers were significantly higher in ICU patients, with a median of 104 AU/ml (3.8–179) compared to 34 AU/ml (3.8–70) in the non-ICU participants (p < 0.0001). Furthermore, the median time to seroconversion occurred significantly faster in ICU patients than in non-ICU participants (19 versus 47 days) (P < 0.0001). IgG titers were also higher in subjects ≥50 years compared to those <50 years (p < 0.009), male compared to female (p < 0.054) and non-Saudi compared to Saudi (p < 0.003). Approximately 74% of all samples tested beyond 120 days were positive.Conclusion: Antibodies can persist in circulation for longer than 4 months after COVID-19 infection. The majority of patients with COVID-19 mounted humoral immune responses to SARS-CoV-2 infection that strongly correlated with disease severity, older age and male gender. However, the population of individuals who tested negative should be further evaluated.